Reconfigurable Wireless Sensor Network Design for Environmental Monitoring in IoT Environment - Myint, Cho Zin (Curtin University, 2018)
This study presents a reconfigurable wireless sensor network (WSN) based water quality monitoring (WQM) system in an IoT environment to measure five parameters of water such as water temperature, water level, water pH, turbidity of water and CO2 on the surface of water using sensors, Field Programmable Gate Array (FPGA), Zigbee wireless communication protocol and personal computer (PC), a VHDL language and C++ program.